2020
DOI: 10.1590/1414-431x20208457
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-tumor efficacy of 5-aminolevulinic acid-gold nanoparticles-mediated photodynamic therapy in cutaneous squamous cell carcinoma cells

Abstract: The objective of this study was to investigate whether the conjugation of gold nanoparticles (GNPs) to 5-aminolevulinic acid (5-ALA) could enhance the anti-tumor efficiency of photodynamic therapy (PDT) in epidermoid carcinoma cells. The mRNA and protein expression levels were determined by quantitative real-time PCR and western blot, respectively. Cell viability, apoptosis, invasion, and migration were determined by MTT assay, flow cytometry, transwell invasion assay, and migration assay, respectively. Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Numerous studies have proven that photosensitizers could be remarkarbly upgraded with better efficiencies under nanotechnological assistance, either in terms of physicochemical properties or biological activity [ 52 ]. For instance, laboratory research indicated that the employment of poly-(lactic-co-glycolic acid) or metal-based nanoparticles as delivery carriers enhanced the uptake of 5-ALA and the following PpIX conversion, which therefore promoted its efficacy [ 53 , 54 , 55 , 56 ]. In a registered 5-ALA gel, 5-ALA was loaded into a nanoscale-lipid vesicle for the treatment of actinic keratosis.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have proven that photosensitizers could be remarkarbly upgraded with better efficiencies under nanotechnological assistance, either in terms of physicochemical properties or biological activity [ 52 ]. For instance, laboratory research indicated that the employment of poly-(lactic-co-glycolic acid) or metal-based nanoparticles as delivery carriers enhanced the uptake of 5-ALA and the following PpIX conversion, which therefore promoted its efficacy [ 53 , 54 , 55 , 56 ]. In a registered 5-ALA gel, 5-ALA was loaded into a nanoscale-lipid vesicle for the treatment of actinic keratosis.…”
Section: Resultsmentioning
confidence: 99%
“…28 In addition, 5-ALA-PDT markedly suppresses cell migration and invasion in A431 cells by enhancing apoptosis in cutaneous squamous cell carcinoma. 29 It has also been reported that Ph1-PDT activates the apoptotic-related proteins caspase-3 and caspase-8, inducing cell apoptosis. 30 Interestingly, our findings showed that Ph1-PDT reduces keloid fibroblast migration and invasion, and promotes apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…This strategy has enabled higher death rates of cancer cells compared to free PS molecules. For some water-soluble second-generation PSssuch as methylene blue (MB) 70 and 5-aminolevulinic acid (5-ALA), 71 they fortunately bypass the problem associated with solubility of first-generation PSs. However, the hydrophilic nature limits the ability to cross lipophilic cell membranes, consequently decreasing the intracellular accumulation of the water-soluble PSs and PDT efficacy.…”
Section: Aunps In Cancer Therapymentioning
confidence: 99%